Types of Inherited Hemoglobin Disorders Among the Patients Attending Hematology Outdoor of a Tertiary Care Hospital in Bangladesh - Rakib, Nur Mohammad; Rishad, Mahbub Mayukh; Zafor Prince, SM Kawser; Jannat, Miftahul; Khan, Tazbiha Rahman; Zinan, Talha Islam; Jeshan, Tanvir; Kabir, Md Alamgir (Journal of Medicine, 2023)
Background: Inherited Haemoglobin (Hb) disorders are the most frequent genetic hereditary disorders with an increasing global health burden, especially in low- and middle-income countries. This disorder is mostly caused by a point mutation on a globin gene resulting mostly in single amino acid substitutions and consequently defective globin chain production or reduced production of normal haemoglobin. Despite the limited study of this country regarding this issue, the number of individuals suffering from inherited Hb disorders is not negligible. Thus, the study was designed to evaluate the types of inherited haemoglobin disorders among the patients attending the haematology outdoor of Dhaka Medical College Hospital (DMCH). Methods: This hospital-based cross-sectional study was conducted at the Department of Haematology in DMCH, for a period of 6 months (June 2022 to November 2022. People attending the Haematology outpatient department and diagnosed with a case of inherited Hb disorder were approached for inclusion. Written informed consent was taken from each subject. Ethical issues were ensured properly. For the study, a total of 100 patients were interviewed for less than 30 minutes of duration in each case. Relevant investigations such as, Hemoglobin (Hb), Red Cell Count (RCC), MCV, MCH, MCHC, RDW, Reticulocyte, Serum ferritin were done in the Haematology lab of DMCH, and data were collected in a semi-structured questionnaire. Collected Data were analyzed by SPSS 21. Results: Out of 100 inherited Hb disorder subjects, the majority (60 or 60%) were from the age group of 14 to 24 years. The mean age of patients was 38.78 ± 6.09 with range 15-51 years. The male-female ratio was 1:1. The majority (58%) came from rural areas and 42% came from urban areas. Mean value of Hb was 10.54; subsequently, MCV (63.25), MCH (22.18), S ferritin (140.43). The majority of patients had their onset of clinical presentation of illness for 5 years. Among total subjects, two-thirds of the patients (66 or 66%) had Hb E Disease followed by 14% Beta thalassaemia trait, 14% Hb E trait, and 6% b thalassaemia major. No association was noted between the type of thalassaemia with age & sex of the subjects. Conclusion: Irrespective of age and sex variations, Hb E disease is the most frequent inherited haemoglobin disorder among the patient attending the haematology outdoor of a tertiary care hospital. J MEDICINE 2023; 24(2): 96-105